Tandem isonitrile insertion/azacyclopropylidene-annulated cyclohexenone–tropone rearrangement of p-QMs and TosMIC: de novo synthesis of pyrrolotropones with anti-cancer activity. Issue 23 (29th September 2021) - Qu, Chuan-Hua; Song, Gui-Ting; Huang, Jiu-Hong; Huang, Run; Chen, Yuan; Liu, Tong; Tang, Dian-Yong; Xu, Zhi-Gang; Chen, Zhong-Zhu
Abstract : TosMIC causes ring expansion of p -QMs: highly substituted pyrrolotropones are rapidly assembled in a domino process mediated by DBU. The utility of the method was highlighted by follow-up transformation and biological activity identification. Abstract : A new and general strategy for the rapid construction of pyrrolotropones via a domino process involving 1, 6-nucleophilic addition, isonitrile insertion, azacyclopropylidene-annulated cyclohexenone to tropone rearrangement, and subsequent aromatization, from the reaction of para -quinone methides ( p -QMs) with p -toluenesulfonylmethyl isocyanide (TosMIC) has been proposed. The reaction does not require transition metals or stoichiometric oxidants and can be performed through one-step operation promoted by a base. This method uses easy-to-synthesize p -QMs and commercially abundant TosMIC and shows excellent scalability and broad substrate scope. Furthermore, the screening of these pyrrolotropone compounds in several human cancer cell lines shows excellent anticancer activity, which validates the feasibility of this protocol for generating bioactive compounds.